Die Geopolitik im Weltbild des Historischen Materialismus - Schöller, Peter (ERDKUNDE, 1959)
Recent publications by J.N. SEMJONOW, H. SANKE and G. HEYDEN show that in the ideology of historical-dialectical materialism geopolitics is accorded a central position in the sense that it is considered the ideological counterpart of the Marxist political and economic geography. Geopolitics is held to be a necessary and integral part of the ideological framework of capitalism in its imperialistic stage of development. It is further alleged that the doctrine of geopolitics arises in all capitalistic countries from the same socio-economic roots and fulfils the same propagandistic function. This examination of the theses and conclusions of historical materialism aims at riding the discussion of all ideological aspects; ist does not by any means intend to whitewash geopolitical ideas which, in Germany in particular, have been responsible for so much harm. In the criticism credit is given to certain potentialities of an interpretation of history as offered by historical materialism. There arises, however, all the more clearly thereby, a clear renunciation in principle of the dogmas of economic determinism and of its totalitarian world picture. What emerges in particular is that historical materialism with its very loose concept of geopolitics embracing everything considered dangerous or inimical creates artificially an ideological counterpart to the economic-historical cliche. This clouding of reality can only impede the necessary fight against the very real geopolitical aberrations and dangers.